Estratégias argumentativas no podcast de mesa redonda: lugar de fala e projeção de identidades no 9° ano do ensino fundamental - Carvalho, Sávio Rebouças de (2024)
This research aims to contribute to the improvement of the discursive practice of students in the 9th year of Elementary School through the use of certain argumentative strategies in a scenario of true social interaction, created from the elaboration and production of a roundtable podcast format. Here, we start from the assumption that the skills of reading, writing and speaking must be worked on in Portuguese language classes not in an exclusionary way, but in a complementary way, since such modalities coexist without hierarchy in the different communicative situations that take place in everyday life, in addition to ratifying the perception that linguistic practice in the digital context does not end with the production of a specific genre: the consequences and implications of its publication are also an important part of the discursive process. To this goal, theoretical contributions were brought to the research regarding discursive genres – such as Bakhtin (2011), Schneuwly and Dolz (2011a, 1011b), Amossy (2020) and Paveau (2021) –, Text Linguistics – highlighting, here, the works of Koch (2007, 2014), Marcuschi (2008, 2012) and Cavalcante and Brito (2022) –, of multiliteracies – highlighting, in this case, Rojo (2012) –, of argumentation and argumentative strategies – such as Abreu (2009), Weston (2009), Fiorin (2015) and Perelman and Olbrechts-Tyteca (2014) – and, in the preparation of the pedagogical notebook, the notions of didactic itinerary found in Dolz, Lima and Zani (2020) and in Barros, Ohuschi and Dolz (2020). This research had as its main method the bibliographical review, and, given its purposes, it was propositional in nature and had a qualitative approach. Its objectives thus point to the need to bring to pedagogical practices – mainly in the context of public schools – discursive genres consistent with the technological and digital dynamics that involve interpersonal relationships in contemporary times, as well as using them as a platform for carrying out practical actions aimed at developing citizen conscience and students' critical and creative capacity through the use of argumentative strategies.